Cross-sectional study of critical incident stress and mental health among firefighters dispatched to areas affected by the Great East Japan Earthquake - KAMIYAMA, Mayuko; WADA, Takako; OKAMOTO, Hiroteru; TSUNODA, Tooru; NOJIMA, Mami (JOURNAL OF THE KYORIN MEDICAL SOCIETY, 2013)
We conducted a survey of 178 firefighters dispatched from other regions to areas affected by the Great East Japan Earthquake of March 11, 2011. From the survey conducted in August 2011, we aimed to evaluate the critical incident stress (CIS) and mental health of the firefighters by using the Impact of Event Scale-revised (IES-R) and other questionnaires. Completed responses were received from 126 subjects (all men; mean age, 40.9 years [range, 22-58 years]), of whom 85 were engaged in the rescue operation of disaster victims, and 41 were engaged in logistics support. The survey results showed that the firefighters were dispatched at an average of 1.6 times (range, 1-6 times) to disaster affected areas, that their IES-R score was 4.0 ± 4.9 (range, 0-21), and that no team member recorded a score of ≥ 25, which is the score considered to show high risk of post-traumatic stress disorder (PTSD). We considered that the reason for none of the firefighters showing risk of PTSD might have been because after they completed their duties, they returned to their home where they were no longer exposed to CIS of this disaster. Considering the various CIS factors of this disaster, the survey results suggest that risk factors for mental health of firefighters dispatched for disaster were “the number of times that they were dispatched,”“participation on the day when a disaster happened,”“rescue operation of disaster victims,” and“staying for long periods in an area affected by a terrible disaster.”